MEANING-OF-LIFE ORIENTATIONS AND REPRESENTATIONS OF MODERN YOUNG PEOPLE CONCERNING THEIR SELF-REALIZATION IN SOCIAL-CULTURAL SPACE OF PSKOV REGION - Gribanova, Diana; Ivanova, Svetlana; Manoilova, Marina; Nikolaev, Alexey (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article raised an important issue of opportunities modern young people in the framework of socio-cultural conditions of the region - the Pskov region. Presents a program of experimental research and its results. Examines the relationship between meaning-of-life and value orientations of graduates of various educational institutions: schools, colleges and the University and attitude toward the past, present and future of the Pskov region and opportunities. The comparative analysis of different groups of graduates in the studied characteristics was done.